2020
DOI: 10.1097/shk.0000000000001618
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Conditioning Reduced Acute Lung Injury After Traumatic Brain Injury in the Mouse

Abstract: Traumatic brain injury (TBI) can induce acute lung injury (ALI). The exact pathomechanism of TBI-induced ALI is poorly understood, limiting treatment options. Remote ischemic conditioning (RIC) can mitigate detrimental outcomes following transplants, cardiac arrests, and neurological injuries. In this study, we hypothesized that RIC would reduce TBI-induced ALI by regulating the sphingosine-1-phosphate (S1P)-dependent pathway, a central regulator of endothelial barrier integrity, lymphocyte, and myokine traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Surgeries/injuries were performed on 16 WT Aged mice. Two WT Aged mice died from brain injury‐induced pulmonary edema <30 min after injury (Saber et al., 2020). Therefore, a total of 30 mice were used for data analyses: 16 3xTg‐AD mice and 14 WT Aged TBI mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeries/injuries were performed on 16 WT Aged mice. Two WT Aged mice died from brain injury‐induced pulmonary edema <30 min after injury (Saber et al., 2020). Therefore, a total of 30 mice were used for data analyses: 16 3xTg‐AD mice and 14 WT Aged TBI mice.…”
Section: Methodsmentioning
confidence: 99%
“…Surgeries/injuries were performed on 16 WT Aged mice. Two WT Aged mice died from brain injuryinduced pulmonary edema <30 min after injury (Saber et al, 2020).…”
Section: Rigormentioning
confidence: 99%
“…Hirsutanol A (HA) has a strong cytotoxic effect as a sessile mushroom compound. Studies have found that HA can induce tumor cell apoptosis by upregulating cleaved-caspase-3, but it is rarely reported in ALI and ARDS [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, during acute lung injury, irisin protects alveolar epithelial cells from damage by maintaining mitochondrial function and improving oxidative stress [ 19 ]. In addition, in the research of brain injury and type 2 diabetes, the effects on antioxidative stress, antiapoptosis, and anti-inflammatory are also described [ 20 , 21 ]. In this study, we first detected serum cytokine levels and found that irisin dramatically reduced the level of inflammation in rats with APID.…”
Section: Discussionmentioning
confidence: 99%